THE SOCIALIZATION OF COMPUTER-BASED NATIONAL ASSESSMENT AT SMPN 2 SIBERUT UTARA - Manganju Manik (Mafaza : Jurnal Pengabdian Masyarakat, 2022)
The Computer-Based National Assessment (ANBK) is a new thing in the world of education in Indonesia. With this ANBK, many responses emerged from the teachers and education staff, parents/guardians, school committees, the community, and students. To respond to this response and provide an explanation about ANBK, the school at SMPN 2 Siberut Utara held a meeting to hold a socialization about ANBK. The method of implementing the ANBK socialization is the lecture and question and answer method. This socialization activity aims to provide knowledge to the participants of the socialization regarding the description of ANBK, management of ANBK implementation, and technical implementation of ANBK. The implementation of ANBK socialization was able to provide understanding to participants regarding ANBK. ANBK socialization is very useful for socialization participants in preparing for the implementation of ANBK in the future.